Optimal and Suboptimal Quadriphase Sequences Derived from Maximal Length Sequences over Z. - Udaya, P.; Siddiqi, M.U.
The paper presents families of quadriphase sequences derived from maximal length sequences over having good correlation properties. These are: (i) families of quadriphase sequences of period from maximal length sequences over ; each family consisting of sequences, (ii) families of quadriphase sequences of period from interleaved maximal length sequences over ; each family consisting of sequences. Such sequences are of interest in quadriphase modulated code division multiple access communication systems, where it is desirable to have large sets of sequences that possess low value of , the maximum magnitude of the periodic crosscorrelation and out of phase auto-correlation values. The sequences over are viewed as trace functions of appropriately chosen unit elements of Galois extension rings of . Quadriphase sequences are then obtained from sequences, by a quadriphase mapping, , from to roots of unity, given by, ; where and . Periodic correlation properties (correlation values and their distribution) of the quadriphase sequences are obtained by using an Abelian association scheme on the elements of the corresponding Galois extension ring of . The majority of the families of sequences derived are optimal with respect to the Welch lower bound on ; the rest being suboptimal with bounded by , where is the period\newpage of the sequences. However nearly half of the sequences in these families are balanced.
Keywords: Sequence design; Pseudorandom sequences; Finite rings; Quadriphase sequences; Periodic correlation; Code-division multiple-access.